Kampanye Online Anti Pornografi: “Pornografi” untuk Kalangan Anak Muda - Darmawan, Andreas James; Putri, Dyah Gayatri (Bina Nusantara University, 2014)
Nowadays, the internet technology is getting an opportunity to visit pornographic sites. Thus, more and more people have a dependency with a pornography site that is not easy to be released. Campaign against pornography